The extent of the use of social networks by university students and their implications for their academic achievement (Field study for a sample of students from the Faculty of Education, Department of Child Education) - كحيلة , مرح عبد الحميد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aimed to measure the extent of social media use among a sample of college students enrolled in the Department of Child Education for the academic year (2020/2019), in addition to identifying the positive and negative effects of their use on their academic achievement, as the study sample consisted of (190) male and female students distributed according to two variables (Gender, and school year). To answer the study's questions and reveal the significance of the differences in the negative and positive effects of the study sample according to the research variables, the descriptive approach was adopted, where the researcher prepared a questionnaire consisting of (31) items distributed on three axes, and the results came as follows: The most used social networks for students is Facebook, and the majority use it to communicate with friends and relatives in addition to seeing local and international news during the evening period, as most of them have more than (300) friends, and subscribers to their favorite site for three to four years. Social networks has a positive impact on university students with a high degree of appreciation. One of the most positive effects of using it is to take advantage of articles and scientific research published by faculty members through it, in addition to accomplishing practical jobs related to practical decisions. Social networks has a negative impact on undergraduates with an average grade, and one of the most negative effects of using them is wasting time allocated to study by talking with friends. There were no statistically significant differences between the averages of students ’answers to the questionnaire axes, according to the sex and school year variables. The study recommended organizing many scientific seminars and educational programs to explain the positive and negative effects of using social networks, in addition to conducting experimental studies and studies to develop communication and electronic communication skills among university students, and work to provide them with electronic research and self-learning skills.